Assessing effectiveness of ABCDE Framework for teaching condylar fracture reduction in dental education: a mixed methods study - Jun Pang; Zhigan Lv; Haifeng Zhang; Siyao Yang; Yuanyuan Wang; Yang Wu; Xiaoxing Hao; Lin Cheng; Pengfei Xin (BMC Medical Education)
Abstract Background Managing displaced proximal segments in mandibular condylar fractures remains challenging due to complex anatomy and limited surgical visibility. Conventional teaching methods in oral and maxillofacial surgery (OMFS) often inadequately address these challenges. This study evaluates the effectiveness of a novel ABCDE educational framework, based on the Technology Acceptance Model (TAM), in enhancing surgical training by improving procedural understanding, technical skill acquisition, and trainee confidence in managing these fractures. Methods The ABCDE framework includes Assessment, Briefing, Collaborative learning, Demonstration, and Evaluation phases. Participants were 39 dental residents (Grades 1–3) enrolled in a 4-month OMFS rotation as part of their clinical residency program. Due to staggered rotation schedules, not all participants had participated in surgical rotations for condylar fracture reduction by the time of the study. All participants completed a two-day training program combining lectures and hands-on sessions. A convergent parallel mixed-methods design was used: quantitative assessments via pre- and post-intervention tests; qualitative analysis of open-ended questionnaires via thematic coding. Statistical analyses were conducted in RStudio using R software. Results Thirty-six participants completed pre- and post-intervention tests and questionnaires, while three did not participate in assessments. Quantitative assessments were conducted using pre- and post-intervention tests, while qualitative analysis was performed on open-ended questionnaires using thematic coding techniques. Following the intervention, students’ test scores demonstrated a significant improvement (median 25.00 [95% confidence interval (CI): 23.75, 30.00] to median 30.00 [95% CI: 25.00, 35.00], p < 0.01). Over 70% of residents reported positive satisfaction and learning gains, with correspondence analysis confirming strong associations between these outcomes. The Net Promoter Score (NPS) for the ABCDE framework was 44.44, indicating moderate-to-high advocacy. Qualitative insights emphasized its practicability, ease of use, and ability to boost engagement and skill acquisition. Conclusions The ABCDE framework bridges theoretical knowledge and hands-on practice, addressing anatomical and technical challenges in teaching mandibular condylar fracture management. Its TAM-driven modular design prioritizes perceived usefulness and perceived ease of use, addressing conventional teaching limitations. Resident feedback emphasized increased satisfaction and advocacy, underscoring the value of interactive, teamwork-focused strategies in medical training.